Fenofibrate Induces Ketone Body Production in Melanoma and Glioblastoma Cells - Grabacka, Maja M.; Wilk, Anna; Antonczyk, Anna; Banks, Paula; Walczyk-Tytko, Emilia; Dean, Matthew; Pierzchalska, Malgorzata; Reiss, Krzysztof (Frontiers in Endocrinology, 2016)
Ketone bodies [beta-hydroxybutyrate (bHB) and acetoacetate] are mainly produced in the liver during prolonged fasting or starvation. bHB is a very efficient energy substrate for sustaining ATP production in peripheral tissues; importantly, its consumption is preferred over glucose. However, the majority of malignant cells, particularly cancer cells of neuroectodermal origin such as glioblastoma, are not able to use ketone bodies as a source of energy. Here, we report a novel observation that fenofibrate, a synthetic peroxisome proliferator-activated receptor alpha (PPARa) agonist, induces bHB production in melanoma and glioblastoma cells, as well as in neurospheres composed of non-transformed cells. Unexpectedly, this effect is not dependent on PPARa activity or its expression level. The fenofibrate-induced ketogenesis is accompanied by growth arrest and downregulation of transketolase, but the NADP/NADPH and GSH/GSSG ratios remain unaffected. Our results reveal a new, intriguing aspect of cancer cell biology and highlight the benefits of fenofibrate as a supplement to both canonical and dietary (ketogenic) therapeutic approaches against glioblastoma.